Inspiratory muscle strength in subjects with tetraplegia: viability of evaluation through the measurement of maximal inspiratory pressure - Marlene Aparecida Moreno; Juliana Viana Paris; Raphael do Nascimento Pereira; Antonio Roberto Zamunér; Tais Mendes de Camargo; Ricardo Machado Leite de Barros
Objective To analyze the values of maximal inspiratory pressure (MIP) and sniff nasal inspiratory pressure (SNIP) and to verify the existence of concordance between the two evaluation methodologies, in subjects with tetraplegia. Materials and methods Cross-sectional study with 17 tetraplegic men, aged 30.42 ± 7.67 years, who underwent MIP and SNIP evaluation using a respiratory pressure meter. Results The MIP and SNIP values obtained showed no difference when compared to each other (88.42 ± 29.39 vs. 86.68 ± 25.40 cmH2O, respectively). They were, however, significantly lower compared to the predicted values (MIP = 128.92 ± 7.18; SNIP = 114.11 ± 3.19 cmH2O), with the MIP values presenting correlation (r2 = 0.94; p < 0.0001) and concordance with those of the SNIP. Conclusions Both the MIP and SNIP values obtained were lower than the predicted values, indicating a reduction in inspiratory muscle strength (IMS). Both techniques showed correlation and concordance, suggesting that MIP can be used as a noninvasive method for IMS evaluation in this population.